2017
DOI: 10.1021/acs.jpcc.7b07395
|View full text |Cite
|
Sign up to set email alerts
|

Near-Electric-Field Tuned Plasmonic Au@SiO2 and Ag@SiO2 Nanoparticles for Efficient Utilization in Luminescence Enhancement and Surface-Enhanced Spectroscopy

Abstract: Application of core−shell plasmonic nanostructures in fluorescence enhancement and surface-enhanced Raman scattering (SERS) strongly depends on their near-field electrodynamical environments. A nonradiative energy transfer takes place between fluorescent molecules and surface plasmon when they are too close. However, for a dielectric shell, the SERS intensity of analytes decreases exponentially beyond 2 nm thickness. Although electromagnetic-field enhancement due to surface plasmon still occurs at longer dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Remarkably, for the thicker shells measured, the SPR shift reaches a maximum value where it saturates. This phenomenon, widely reported for the other similar systems, relates to the maximum distance to which the local field extends from NP's surface [27,28]. Similarly, the broadening of the plasmon band as the CeO2 shell thickness increases can be associated with the non-compact nature of the CeO2 shell coating.…”
Section: Synthesis Of Au@ceo2 Hybrid Nanocrystalssupporting
confidence: 55%
See 1 more Smart Citation
“…Remarkably, for the thicker shells measured, the SPR shift reaches a maximum value where it saturates. This phenomenon, widely reported for the other similar systems, relates to the maximum distance to which the local field extends from NP's surface [27,28]. Similarly, the broadening of the plasmon band as the CeO2 shell thickness increases can be associated with the non-compact nature of the CeO2 shell coating.…”
Section: Synthesis Of Au@ceo2 Hybrid Nanocrystalssupporting
confidence: 55%
“…This assumption determines the effective dielectric constant of the system, which ultimately affects the extent on the SPR red-shifts. (SERS) requires the study of the optimum shell thickness for obtaining the maximum near-field enhancement at the core-shell and shell-medium interfaces [28]. Moreover, the plasmonic enhancement is particularly interesting for the study of plasmon resonances at their fundaments, including nonlinear optical processes such as second harmonic generation [31].…”
Section: Synthesis Of Au@ceo2 Hybrid Nanocrystalsmentioning
confidence: 99%
“…As can be seen from Figure 6a, the substrate prepared with Ag@Au nanodisks exhibits much enhanced Raman signals in comparison to the Raman signal intensities obtained from their solution-casted counterpart. Apart from the effect of dispersion media (air in the first case and water in the second case), 64 the substrate-based assembly of plasmonic nanostructures seems to be of help in producing uniform and more intense “hot spots” which are responsible for the enhancement of Raman signal of the analytes. The Ag@Au nanodisks revealed highly intense Raman signals in comparison to the Ag NPLs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to these approaches, various studies were performed to verify the effect of spatial variation by controlling spacing within shell thickness. For example, Montaño-Priede et al demonstrated that the maximum fluorescence enhancement of quantum dots (QDs, CdSe) was observed when a silica shell between a GNP core and QDs was approximately 10 nm; however, both the reduction and the increase of shell thickness diminished the enhancement effect of the fluorescence either by energy transfer from the QDs to GNP or a larger separation between the CdSe QDs and GNP core, respectively ( Figure 3 D) [ 53 ].…”
Section: Gold Nanoparticle-based Plasmon-enhanced Fluorescence Andmentioning
confidence: 99%